2010
DOI: 10.1007/s10750-010-0158-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term trends in water temperature and ice cover in the subalpine lake, Øvre Heimdalsvatn, and nearby lakes and rivers

Abstract: Long-term data series of ice cover on lakes and river temperatures from the mountain areas of Norway are lacking. The present study analyses the last four decades of ice data from the subalpine lake, Øvre Heimdalsvatn, and water temperature data from its outlet river, Hinøgla. These data are compared to water temperature data from three neighbouring, quite different locations, the glacier-fed rivers Leirungsåi and Sjoa, and the alpine lake, Bessvatn. The study also examines the air temperature/river temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 44 publications
2
28
0
Order By: Relevance
“…The lake surface temperature may reach more than 17°C during summer (Kloster, 1978), and monthly means up to or above 16°C have been recorded in the outlet during some recent years (Kvambekk & Melvold, 2010). Lake temperatures in autumn have increased by 1.4°C during the last 10 years, with a 3°C increase in September temperatures.…”
Section: Methodsmentioning
confidence: 99%
“…The lake surface temperature may reach more than 17°C during summer (Kloster, 1978), and monthly means up to or above 16°C have been recorded in the outlet during some recent years (Kvambekk & Melvold, 2010). Lake temperatures in autumn have increased by 1.4°C during the last 10 years, with a 3°C increase in September temperatures.…”
Section: Methodsmentioning
confidence: 99%
“…It is shallow, with a maximum depth of 13 m. The hydrological regime of the lake contrasts between the spring spate when lake waters are renewed within a few days to a situation with very low water inputs during the winter, when lake waters are barely renewed (Larsson et al, 1978). The lake is ice covered from late October until the beginning of June (Kvambekk & Melvold, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…In 1986, ice break took place around 8 June (Kvambekk & Melvold, 2010). Studies of the initial contamination of brown trout (Salmo trutta) (Brittain et al, 1991) showed a gradual increase in activity concentrations of 137 Cs in brown trout during the summer of 1986, culminating in a maximum mean activity concentration of 7,200 Bg/kg w.w. in late August.…”
Section: Introductionmentioning
confidence: 99%
“…While warming lake temperatures from longer ice free seasons could alter the lake stratification (e.g. Kvambekk and Melvold, 2010;Mueller et al, 2009) an assumption was made that the mixed layer remained constant in the future simulations. In order to represent potential changes to the mixed layer a lake model such as the Freshwater Lake model (FLake: Mironov, 2008) could be used to provide mixed layer information for CLIMo (Kheyrollah Pour et al, 2011).…”
Section: Lake Ice Modelmentioning
confidence: 99%